UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI POKOK LIMIT DI KELAS XII RPL 2 SMK AL-IHSAN BATUJAJAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Rohmah, Tsaani Septi; Nuraida, Riski; Agnesti, Yuni (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research goals to fix the activeness and knowing results of students using the STAD type cooperative learning model on the subject matter of algebraic function limits. The points of this research were students of grade XII RPL 2 SMK AL-Ihsan Batujajar with a total of 26 students, consisting of 9 male students and 17 female students. The instrument used in this study was the observation sheet and the test description and interview of the mathematics teacher at the school. The results of student activeness research in the first cycle of 65.38% were in the criteria of being quite active, and the second cycle at 84.61% were in active criteria. And the results of research on student learning outcomes in the first cycle is in the percentage of class completeness by 53.84% and in the second cycle is the percentage of class completeness by 92.30%, it can be seen student learning outcomes from cycle I has intensified in cycle II. Based on the research outcomes, it can be resumed that the use of the STAD type of cooperative upgrading on the subject of algebraic functional limit in class XII RPL 2 SMK AL-Ihsan Batujajar there is an influence of increasing student learning outcomes and activeness.